Oltre il sinfonismo musicale čajkovskiano. Note di studio sui processi compositivi di Petipa ne “La bella addormentata” - Marta Mele (Danza e Ricerca)
When a philological reconstruction of the ballet The Sleeping Beauty was staged in St. Petersburg in 1999, there were numerous criticisms against the production. According to the scholar Tim Scholl, this version had revealed the limits of Soviet dance and in particular «the failure of its central dogma, symphonism». After having retraced the history of this ballet and after having reread the studies on Pyotr Tchaikovsky's musical symphonism, the author of the essay aims to delve deeper into the substance of the purely choreographic symphonism created by Marius Petipa. The writings of the Soviet choreographer and theorist Fyodor Lopuchov prove fundamental in this regard. The questions he raises open the way to new research.